1997
DOI: 10.1089/jwh.1997.6.163
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Immunodeficiency Virus Infection and Drug Use in Pregnant Women: A Critical Review of the Literature

Abstract: Many studies have been undertaken in the last 10 years to determine the prevalence of both human immunodeficiency virus (HIV) infection and drug use in pregnant women. These studies could have a serious impact on the delivery of health care as well as the development of health policy. We provide an overview of the key findings from these studies and a critical review of their strengths and weaknesses. For example, although many prevalence studies were conducted with enough participants to reach statistical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Research on HIV seroprevalence in childbearing women demonstrated that risk‐directed testing (testing only those with reported risk factors) is an inadequate method of identifying women who may give birth to HIV‐infected infants. In a review of the literature, Abercrombie and Booth (96) found that there was not one specific “type” of woman who was likely to be HIV infected, no particular group of women that could justly be held accountable for the increasing numbers of perinatal/pediatric AIDS cases, and no group that could be assured of immunity from infection with HIV.…”
Section: Management Of Pregnant Women With Hiv Infections: a Double Smentioning
confidence: 99%
“…Research on HIV seroprevalence in childbearing women demonstrated that risk‐directed testing (testing only those with reported risk factors) is an inadequate method of identifying women who may give birth to HIV‐infected infants. In a review of the literature, Abercrombie and Booth (96) found that there was not one specific “type” of woman who was likely to be HIV infected, no particular group of women that could justly be held accountable for the increasing numbers of perinatal/pediatric AIDS cases, and no group that could be assured of immunity from infection with HIV.…”
Section: Management Of Pregnant Women With Hiv Infections: a Double Smentioning
confidence: 99%